Antidiabetic Activity of Green Seaweed (Eucheuma spinosum) Ethanol Extract in Alloxan Induced Male White Rats (Rattus norvegicus) - Rachmadhiani, Ana Noviana; Rahayuningsih, Nur; Nuryadin, Dichy (Jurnal Ilmiah Farmako Bahari, 2025)
Diabetes is a long-term metabolic disorder with a globally increasing prevalence, including in Indonesia. This study aims to evaluate the antidiabetic effects of the ethanol extract of Eucheuma spinosum on alloxan-induced rats in vivo. This study used an experimental design with 24 rats divided into six groups, namely the normal control group, positive control (metformin 9 mg/200 g body weight), negative control, and three treatment groups receiving Eucheuma spinosum extract at doses of 30, 60, and 120 mg/200 g body weight. The extract was obtained through the maceration method and contains active compounds such as alkaloids, flavonoids, saponins, and tannins. Blood glucose measurements were taken before and after the treatment. The yield of the extract obtained was 2.5%. The highest dose, 120 mg/200 g body weight of the rats, resulted in the most significant decrease in blood glucose levels by 39.705%. Statistical analysis using ANOVA showed a significant difference (p ≤ 0.05) between the treatment and negative control groups. The antidiabetic activity of this extract is suspected to originate from its flavonoid and saponin content, which stimulate the regeneration of pancreatic β cells and inhibit glucose absorption in the digestive tract. Ethanol extract of Eucheuma spinosum is effective in lowering blood glucose levels in diabetic rats and has the potential to be developed as a natural antidiabetic agent.